Chinese physical fitness standard for campus football players: A pilot study of 765 children aged 9 to 11 - Jia, Hong; Wan, Bin; Bu, Te; Luo, Yang; Ma, Weiping; Huang, Sen; Gang, Liang; Deng, Wei; Liu, Zeyong (Frontiers in Physiology, 2022)
Objectives: In 2022, 55 million Chinese children participate in campus football; however, there is no physical fitness standard, making it a priority task to enhance the current national program. This study aimed to explore a pilot method for the development of a reliable physical fitness standard. Methods: This study examined 765 male football players aged 9 to 11 in 2020 and 2022. The anthropometric and physical fitness assessments were conducted in accordance with the Chinese Football Association's field manuel. Physical fitness tests include sit and reach test, T test, 30m run test, and vertical jump test. Physical fitness standard was modeled using the generalized additive models for location, scale, and shape (GAMLSS). Data were fitted with appropriate GAMLSS distributions and smoothing term. P-splines were applied to smooth the model's parameters using the default local maximum likelihood method and link functions. Following diagnostics of fitted models, age-specific centile estimations were computed for physical fitness tests. In addition, players in each age group were categorized according to their body mass index as normal weight or overweight/obese. Welch's t-test was utilized to compare the group differences in physical fitness testing. The significance level was chosen at P < 0.05. Results: Sit and reach test, T test, 30m run test, and vertical jump test data were fitted with original Sinh-Arcsinh, Box-Cox power exponential, Box-Cox power exponential, and Box-Cox Cole and Green, respectively. Physical fitness standard for each age group is presented as tabulated centiles (1p, 3p, 5p, 15p, 25p, 50p, 75p, 85p, 95p, 97p, 99p). Overweight/obese campus football players did significantly worse (P < 0.05) on the T test, 30m run test, and vertical jump test than their normal-weight peers of the same age. Conclusion: This study developed the first physical fitness standard for 9 to 11-year-old campus football players in China. We made three recommendations to Chinese policymakers on sample size, data management, and field procedure for the creation of a national physical fitness standard.